A new species of Rhabdias (Nematoda: Rhabdiasidae), a lung parasite of Pseudopaludicola pocoto (Anura: Leptodactylidae) from north-eastern Brazil: description and phylogenetic analyses - Morais, D. H.; Müller, M. I. [UNESP]; Melo, F. T.V.; Aguiar, A. [UNESP]; Willkens, Y.; de Sousa Silva, C.; Giese, E. G.; Ávila, R. W.; da Silva, Reinaldo José [UNESP] (Cambridge University Press (CUP), 2020)
Rhabdias pocoto n. sp. is herein described from the lungs of the swamp frog Pseudopaludicola pocoto Magalhães, Loebmann, Nogueira, Kokubum, Baptista, Haddad & Garda, 2014, from the Caatinga biome in the state of Ceará, in north-eastern Brazil. The new species is characterized by a body that dilates posteriorly, six small lips (protuberances) and two rounded lateral expansions of cuticular inflation on the anterior end, each containing an amorphous gland-like structure inside and a short and conical tail. Additionally, molecular analysis and comparison of the partial mitochondrial cytochrome c oxidase I sequence of R. pocoto n. sp. revealed genetic divergence between the new species and the sequences of Rhabdias spp. previously deposited in GenBank. Phylogenetic analysis grouped the new taxon into the R. pseudosphaerocephala species complex + R. glaurungi clade. The new discovery represents the 19th species of Rhabdias spp. described in the Neotropical region, the ninth in Brazil and the first species of Rhabdias found parasitizing South American frogs of the genus Pseudopaludicola, as well as the first Caatinga biome species of Rhabdias.
Keywords: Caatinga biome; COI gene; nematodes; Rhabdias phylogeny